Reduced Perinatal Leptin Availability May Contribute to Adverse Metabolic Programming in a Rat Model of Uteroplacental Insufficiency - Nuesken, Eva; Wohlfarth, Maria; Lippach, Gregor; Rauh, Manfred; Schneider, Holm; Doetsch, Joerg; Nuesken, Kai-Dietrich (Endocrinology, 2016)
Leptin availability in perinatal life critically affects metabolic programming. We tested the hypothesis that uteroplacental insufficiency and intrauterine stress affect perinatal leptin availability in rat offspring. Pregnant rats underwent bilateral uterine vessel ligation (LIG; n = 14), sham operation (SOP; n = 12), or no operation (controls, n = 14). Fetal livers (n = 180), placentas (n = 180), and maternal blood were obtained 4 hours (gestational day [E] 19), 24 hours (E20), and 72 hours (E22) after surgery. In the offspring, we took blood samples on E22 (n = 44), postnatal day (P) 1 (n = 29), P2 (n = 16), P7 (n = 30), and P12 (n = 30). Circulating leptin (ELISA) was significantly reduced in LIG (E22, P1, P2) and SOP offspring (E22). Postnatal leptin surge was delayed in LIG but was accelerated in SOP offspring. Placental leptin gene expression (quantitative RT-PCR) was reduced in LIG (E19, E20, E22) and SOP (E20, E22). Hepatic leptin receptor (Lepr-a, mediating leptin degradation) gene expression was increased in LIG fetuses (E20, E22) only. Surprisingly, hypoxia-inducible factors (Hif; Western blot) were unaltered in placentas and were reduced in the livers of LIG (Hif1a, E20; Hif2a, E19, E22) and SOP (Hif2a, E19) fetuses. Gene expression of prolyl hydroxylase 3, a factor expressed under hypoxic conditions contributing to Hif degradation, was increased in livers of LIG (E19, E20, E22) and SOP (E19) fetuses and in placentas of LIG and SOP (E19). In summary, reduced placental leptin production, increased fetal leptin degradation, and persistent perinatal hypoleptinemia are present in intrauterine growth restriction offspring, especially after uteroplacental insufficiency, and may contribute to perinatal programming of leptin resistance and adiposity in later life.
EVALuna2:33880